Pyrochlore type A2-xBxZr2O7 transparent ceramic material and preparation method thereof
Through the preparation of calcinedite-type A2-xBxZr2O7 transparent ceramic materials, combined with solid phase method and vacuum sintering process, the shortcomings of existing transparent ceramic materials in optical performance and industrial production are solved, and high optical transmittance and suitable for industrial production are achieved.
Patent Information
- Application Number
- CN202411968099.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-22
AI Technical Summary
The existing transparent ceramic materials have shortcomings in optical performance and industrial production, and it is difficult to meet different application needs.
The calcinedite-type A2-xBxZr2O7 transparent ceramic material is used to prepare powder and vacuum sintering process through solid phase method, and combined with rare earth doping technology, materials with high optical transmittance and suitable for industrial production are prepared.
It has achieved high raw material utilization and high optical transmittance, and can meet different application needs through rare earth doping, and is suitable for optical isolators and X-ray radiation detection devices and other fields.
Smart Images

Figure CN119859061A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of transparent ceramic materials, and particularly relates to a pyrochlore-type A 2-x B x Zr2O7 transparent ceramic material and its preparation method, in particular, it relates to oxide transparent ceramic material contained in magneto-optical equipment suitable for optical isolators and its preparation method, and it relates to oxide transparent ceramic material contained in X-ray radiation detection devices and its preparation method. Background Art
[0002] In recent years, with the rapid development of transparent ceramic preparation technology, the advantages of transparent ceramics in mechanics, optics, thermals, etc. have become increasingly prominent, and it has also provided a new way for the development of optoelectronic functional materials. Due to its excellent optical properties, high hardness and other advantages, it has good application potential in the field of optics. In recent years, the research on new transparent ceramic materials has become a goal that scientists continue to pursue and explore. A2B2O7 system materials were first discovered in the 1960s and have been found to be used as thermal barrier coatings, luminescent powders, fast ion conductors, photocatalysts, and matrices for immobilizing highly active radioactive nuclides. [1–5] From the structural analysis, it is found that in the cubic compound of A2B2O7, the crystal structure changes with r A and r B The ionic radius ratio (r A / r B ), temperature, and pressure, among which the most common structures are pyrochlore phase and defective fluorite phase. A / r B is the most important factor in determining the crystal structure of the compound, according to Subramanian
[19] Reported that when A / r B =1.46~1.78, the A-site and B-site ions are arranged in an orderly manner, and this structure is called an ordered pyrochlore structure; when r A / r B When r is less than 1.46, the cations will be arranged disorderly to form a stable defective fluorite structure. A / r B When the ratio is greater than 1.78, a monoclinic structure is formed. Since the A and B positions can occupy different chemical elements, the system can generate more than 150 types of compounds. Summary of the invention
[0003] The present invention provides a pyrochlore type A 2-x B x Zr2O7 transparent ceramic material and preparation method thereof solve the defects of the prior art.
[0004] In order to solve the above technical problems, the present invention provides a pyrochlore type A 2-x B x Zr2O7 transparent ceramic material, characterized in that: A and B are independently selected from at least one of the trivalent elements Gd, Eu, Al, and Tb, the transparent ceramic prepared using Gd, Eu, and Al has X-ray detection capabilities, and the transparent ceramic prepared using Tb has magneto-optical properties.
[0005] A pyrochlore type A 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by comprising two process steps of preparing powder by solid phase method and preparing transparent ceramic material by vacuum sintering.
[0006] The specific method for preparing the powder is as follows:
[0007] The required raw materials were weighed according to the stoichiometric ratio, loaded into a ball mill, and zirconium oxide balls, anhydrous ethanol and polyethylene glycol were added. After ball milling for a certain period of time, the mixture was placed in an oven, and then the dried powder was sieved. The obtained powder was then sintered in a box furnace, and the temperature was increased to 1200-1500°C at 2-3°C / min and kept for 5-8h. The above operation was repeated again to obtain A 2-x B x Zr2O7 polycrystalline powder; the polycrystalline powder is pressed into a round blank with a diameter of 10 to 60 mm and a thickness of 3 to 10 mm by a hydraulic press, and then the blank is vacuum packaged, and finally the packaged blank is cold isostatically pressed at 200 to 250 MPa for 2 to 3 minutes to complete the blank plasticity.
[0008] The plasticized green embryo is heated to 600-900°C at 2-3°C / min and kept at a constant temperature for 5-6 hours. The zirconia powder and green embryo samples are placed in a tungsten crucible and sintered in a vacuum tungsten wire furnace. The temperature is increased at 2-3°C / min and kept at a temperature range of 1800-1850°C for 10-50 hours. After sintering, it is placed in a box furnace for annealing, heated to 1200-1450°C at 2-3°C / min, kept at a constant temperature for 10-30 hours, and finally slowly cooled to room temperature.
[0009] Beneficial effects:
[0010] 1) Pyrochlore type A provided in this application 2-x B x Zr2O7 transparent ceramic material has high raw material utilization rate and high optical transmittance, and can be doped with a variety of rare earths to form pyrochlore A 2-x B x Zr2O7 transparent ceramic materials are modified to meet different application requirements.
[0011] 2) Pyrochlore type A provided in this application2-x B x The invention relates to a method for preparing Zr2O7 ceramic material. The method prepares powder by a solid phase method, and then prepares transparent ceramic material by sintering in a vacuum tungsten wire furnace. In particular, in the raw material preparation process, a secondary ball milling process is adopted to obtain powder with a more uniform particle size, and then vacuum sintering is performed to prepare a transparent ceramic material with high transmittance. The method has the advantages of being simple and efficient, having a high raw material utilization rate, and being suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 In Examples 1 to 5 of the present application, pyrochlore type A 2-x B x Zr2O7 transparent ceramic material preparation process diagram.
[0013] Figure 2 In Examples 1 to 4 of the present application, pyrochlore type A 2-x B x X-ray powder diffraction pattern of Zr2O7 transparent ceramic powder.
[0014] Figure 3 In Examples 1 to 4 of the present application, pyrochlore type A 2-x B x Transmittance diagram of Zr2O7 transparent ceramics, where (a), (b), (c), and (d) are the transmittance curves of Gd2Zr2O7 at different sintering temperatures, the transmittance curves of Gd2Zr2O7 at different Eu doping concentrations, and the transmittance curves of Zr2O7 at different sintering temperatures. 2- x Eu x Zr2O7 transmittance curve, Gd prepared by sintering at 1800℃ 1.78 Al 0.02 Eu 0.2 Zr2O7 transmittance curve, Eu2Zr2O7 transmittance curve at different sintering temperatures.
[0015] Figure 4 In Examples 1 to 5 of the present application, pyrochlore type A 2-x B x The actual picture of Zr2O7 transparent ceramics, where (a), (b), (c), (d), and (e) are the actual pictures of Gd2Zr2O7 at different sintering temperatures, Gd2Zr2O7 with different Eu doping concentrations, 2-x Eu x Zr2O7 physical picture, Gd prepared by sintering at 1800℃ 1.78 Al 0.02 Eu 0.2 Physical picture of Zr2O7, physical picture of Eu2Zr2O7 at different sintering temperatures, physical picture of Tb2Zr2O7 at different sintering temperatures. DETAILED DESCRIPTION
[0016] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below.
[0017] A pyrochlore type A proposed by the present invention 2-x B x Zr2O7 transparent ceramic material, wherein A and B are independently selected from trivalent elements, selected from at least one of Gd, Eu, Al, and Tb. Transparent ceramics prepared by using Gd, Eu, and Al have X-ray detection capabilities, and transparent ceramics prepared by using Tb have magneto-optical properties. Therefore, according to actual needs, transparent ceramic materials for different applications can be prepared by using different rare earth ion doping.
[0018] 0≤x≤2.
[0019] The crystal structure is cubic.
[0020] The present invention provides a pyrochlore type A 2-x B x The method for preparing Zr2O7 transparent ceramic material includes two process steps of preparing powder by solid phase method and preparing transparent ceramic material by vacuum sintering, as follows
[0021] S1. According to the stoichiometric ratio, weigh A2O3, B2O3 rare earth oxide and ZrO2 and put them into a zirconia ball ink tank, add zirconia balls (large ball diameter 10-12mm, medium ball diameter 6-8mm, small ball diameter 2-5mm, large, medium and small ball mass ratio of 1-2:5-6:2-3, total mass of zirconia balls and raw material mass ratio of 25-28:1), anhydrous ethanol (100-150ml) and polyethylene glycol (PEG400, 2-5ml), ball mill in a planetary ball mill for 48-72 hours, place the mixture in an oven (temperature 70-90°C, 24-48 hours), take out the sample, sieve the dried powder with a 200-400 mesh screen, then put the obtained powder into a box furnace for sintering, raise the temperature to 1200-1500°C at 2-3°C / min and keep it warm for 5-8h, repeat the above operation again, and finally obtain A 2-x B x Zr2O7 polycrystalline powder. Take 2-30g of the above powder and use a hydraulic press (pressure of 10Pa-30Pa) to press it into a round blank with a diameter of 10-60mm and a thickness of 3-10mm. Then vacuum seal the blank and finally perform cold isostatic pressing at 200-250Mpa for 2-3min to complete the blank plasticity. The content of anhydrous ethanol and polyethylene glycol is determined according to the capacity of the ball ink tank. The amount of anhydrous ethanol added does not exceed two-thirds of the total volume of the ball ink tank. A small amount of polyethylene glycol acts as a ball ink medium to mix the raw materials evenly. It is determined based on experience.
[0022] S2. Place the plasticized green embryo in a muffle furnace and heat it to 600-900℃ at 2-3℃ / min and keep the temperature constant for 5-6h. Then place the green embryo and zirconium oxide powder in a tungsten crucible in the order of zirconium oxide powder (100-200g), green embryo, and zirconium oxide powder (100-200g). -4 ~5×10 -5 MPa), the temperature is increased by 2-3°C / min, and the temperature is kept at 1800-1850°C for 10-50h. After sintering, the sample is placed in a box furnace for annealing, and the temperature is increased by 2-3°C / min to 1200-1450°C, and the temperature is kept constant for 10-30h to eliminate internal defects, and finally the temperature is slowly lowered to room temperature, and the sample is taken out to complete the ceramic preparation. The number of blanks is determined according to needs, and its ratio to zirconium oxide powder belongs to the empirical value in the field, and does not belong to the innovation of the present invention.
[0023] The specific preparation process can refer to the process preparation method in the examples.
[0024] Optionally, the pyrochlore type A 2-x B x The sintering temperature of Zr2O7 powder is independently selected from any value among 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃ or the range between any two of the above values.
[0025] Optionally, the pyrochlore type A 2-x B x The pressure of dry pressing of Zr2O7 powder is 10Pa~30Pa.
[0026] Optionally, the pyrochlore type A 2-x B x The sintering temperature of the Zr2O7 transparent ceramic material is independently selected from any value among 1700℃, 17300℃, 1750℃, 1780℃, 1800℃, 1850℃ or a range between any two of the above values.
[0027] Optionally, the pyrochlore type A 2-x B x The vacuum degree during sintering of Zr2O7 transparent ceramic material is independently selected from 3×10 - 4 MPa, 5×10 -4 MPa, 8×10 -4 MPa, 3×10 -4 MPa, 5×10 -5 Any value in MPa or a range between any two of the above.
[0028] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0029] Example 1
[0030] This embodiment provides a method for preparing a pyrochlore-type Gd2Zr2O7 transparent ceramic material, and the specific steps are as follows:
[0031] (1) Gd2Zr2O7 powder was prepared by the following specific steps: high-purity ZrO2 (Aladdin, purity 99.99%) and Gd2O3 (Changting Jinlong Rare Earth, purity 99.99%) were accurately weighed in a glove box according to the stoichiometric ratio. These raw materials (30 g) were placed in a zirconia ball mill, and zirconia balls (810 g in total) were added, wherein the ratio of large balls (10 mm in diameter), medium balls (8 mm in diameter), and small balls (3 mm in diameter) was 2:5:3, and the ball-to-material mass ratio was 27:1. , add dispersant polyethylene glycol (PEG400, dosage: 3 ml) and solvent anhydrous ethanol (C2H6O, dosage: 120 ml), place it in a planetary ball mill, and after ball milling for 72 hours, put the mixture into a drying oven and keep it at 70°C for 24 hours. Then put it into a box furnace for sintering, increase the temperature to 1400°C at 3°C / min and keep it for 5 hours. Take out the sample, repeat the above steps again, and finally sieve the powder with a stainless steel sieve (200 mesh) to obtain polycrystalline powder.
[0032] (2) Weigh 2.5 g of the polycrystalline powder obtained in step (1) and put it into a mold with a diameter of 25 mm. Use a hydraulic press to press the powder into a round blank with a diameter of 20 mm and a thickness of 4 mm after isostatic pressing at 12 MPa for 3 min. Then, vacuum seal the blank and finally perform cold isostatic pressing at 200 MPa for 3 min to complete the plasticization of the blank.
[0033] (3) The plasticized green blank was placed in a muffle furnace and heated to 600°C at 3°C / min and kept at this temperature for 5 h. The green blank and zirconium oxide powder were then placed in a tungsten crucible in the order of zirconium oxide powder (150 g), green blank, and zirconium oxide powder (150 g). -5 MPa), the temperature was raised at 3°C / min, and the temperature was kept at 1800-1850°C for 10 hours. After sintering, the sample was placed in a box furnace for annealing, the temperature was raised to 1250°C at 2°C / min, and the temperature was kept constant for 10 hours to eliminate internal defects, and finally the temperature was slowly lowered to room temperature, and the sample was taken out to complete the ceramic preparation.
[0034] (4) The ceramic sample is placed in a double-sided polishing machine for double-sided polishing. After polishing, the ceramic sample has a diameter of 20 mm and a thickness of 2.5 mm.
[0035] Example 2
[0036] This example provides a pyrochlore-type Gd 2-x Eu x The preparation method of Zr2O7 (x=0.04, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28) transparent ceramic material, the specific steps are as follows:
[0037] (1) Gd2Zr2O7 powder was prepared by the following specific steps: high-purity ZrO2 (Aladdin, purity 99.99%), Gd2O3 (Changting Jinlong Rare Earth, purity 99.99%), and Eu2O3 (Changting Jinlong Rare Earth, purity 99.99%) were accurately weighed in a glove box according to the stoichiometric ratio. These raw materials (30 g) were placed in a zirconia ball mill, and zirconia balls (810 g in total) were added, wherein the ratio of large balls (diameter 10 mm), medium balls (diameter 8 mm), and small balls (diameter 3 mm) was 2:5: 3. The ball-to-material mass ratio is 27:1. Add dispersant polyethylene glycol (PEG400, dosage: 3 ml) and solvent anhydrous ethanol (C2H6O, dosage: 120 ml), place in a planetary ball mill, and after ball milling for 72 hours, put the mixture into a drying oven and keep it at 70°C for 24 hours. Then put it into a box furnace for sintering, increase the temperature to 1400°C at 3°C / min and keep it warm for 5 hours. Take out the sample and repeat the above steps again. Finally, sieve the powder with a stainless steel sieve (200 mesh) to obtain polycrystalline powder.
[0038] (2) Weigh 2.5 g of the polycrystalline powder obtained in step (1) and put it into a mold with a diameter of 25 mm. Use a hydraulic press to press the powder into a round blank with a diameter of 20 mm and a thickness of 4 mm after isostatic pressing at 12 MPa for 3 min. Then, vacuum seal the blank and finally perform cold isostatic pressing at 200 MPa for 3 min to complete the plasticization of the blank.
[0039] (3) The plasticized green blank was placed in a muffle furnace and heated to 600°C at 3°C / min and kept at this temperature for 5 h. The green blank and zirconium oxide powder were then placed in a tungsten crucible in the order of zirconium oxide powder (150 g), green blank, and zirconium oxide powder (150 g). -5 MPa), the temperature was raised at 3°C / min, and the temperature was kept at 1800-1850°C for 10 hours. After sintering, the sample was placed in a box furnace for annealing, the temperature was raised to 1250°C at 2°C / min, and the temperature was kept constant for 10 hours to eliminate internal defects, and finally the temperature was slowly lowered to room temperature, and the sample was taken out to complete the ceramic preparation.
[0040] (4) The ceramic sample is placed in a double-sided polishing machine for double-sided polishing. After polishing, the ceramic sample has a diameter of 20 mm and a thickness of 2.5 mm.
[0041] Example 3
[0042] This example provides a pyrochlore-type Gd 1.78 Al 0.02 Eu 0.2 The preparation method of Zr2O7 transparent ceramic material, the specific steps are as follows:
[0043] (1) Preparation of Gd 1.78 Al 0.02 Eu 0.2 Zr2O7 powder, the specific steps are as follows: according to the stoichiometric ratio, high-purity ZrO2 (Aladdin, purity 99.99%), Eu2O3 (Changting Jinlong Rare Earth, purity 99.99%), Al2O3 are accurately weighed in a glove box, these raw materials (30g) are loaded into a zirconia ball mill, and zirconia balls (810g in total) are added, wherein the ratio of large balls (diameter 10mm), medium balls (diameter 8mm), and small balls (diameter 3mm) is 2:5:3, and the ball-to-material mass ratio is 27:1, Add dispersant polyethylene glycol (PEG400, dosage: 3 ml) and solvent anhydrous ethanol (C2H6O, dosage: 120 ml), place in a planetary ball mill, and after ball milling for 72 hours, put the mixture into a drying oven and keep it at 70°C for 24 hours. Then put it into a box furnace for sintering, increase the temperature to 1400°C at 3°C / min and keep it for 5 hours. Take out the sample and repeat the above steps again. Finally, sieve the powder with a stainless steel sieve (200 mesh) to obtain polycrystalline powder.
[0044] (2) Weigh 15 g of the polycrystalline powder obtained in step (1) and load it into a mold with a diameter of 40 mm. Use a hydraulic press to press the powder into a round blank with a diameter of 40 mm and a thickness of 4 mm after isostatic pressing at 12 MPa for 3 min. Then, vacuum seal the blank and finally perform cold isostatic pressing at 200 MPa for 3 min to complete the blank plasticization. The final blank diameter is 36.23 mm.
[0045] (3) The plasticized green blank was placed in a muffle furnace and heated to 600°C at 3°C / min and kept at this temperature for 5 h. The green blank and zirconium oxide powder were then placed in a tungsten crucible in the order of zirconium oxide powder (150 g), green blank, and zirconium oxide powder (150 g). -5 MPa), the temperature was raised at 3°C / min, and the temperature was kept at 1800-1850°C for 10 hours. After sintering, the sample was placed in a box furnace for annealing, the temperature was raised to 1250°C at 2°C / min, and the temperature was kept constant for 10 hours to eliminate internal defects, and finally the temperature was slowly lowered to room temperature, and the sample was taken out to complete the ceramic preparation.
[0046] (4) The ceramic sample is placed in a double-sided polishing machine for double-sided polishing. After polishing, the ceramic sample has a diameter of 20 mm and a thickness of 2.5 mm.
[0047] Example 4
[0048] This embodiment provides a method for preparing a pyrochlore-type Eu2Zr2O7 transparent ceramic material, and the specific steps are as follows:
[0049] (1) Eu2Zr2O7 powder was prepared by the following specific steps: high-purity ZrO2 (Aladdin, purity 99.99%) and Eu2O3 (Changting Jinlong Rare Earth, purity 99.99%) were accurately weighed in a glove box according to the stoichiometric ratio. These raw materials (30 g) were placed in a zirconia ball mill, and zirconia balls (810 g in total) were added, wherein the ratio of large balls (10 mm in diameter), medium balls (8 mm in diameter), and small balls (3 mm in diameter) was 2:5:3, and the ball-to-material mass ratio was 27:1. , add dispersant polyethylene glycol (PEG400, dosage: 3 ml) and solvent anhydrous ethanol (C2H6O, dosage: 120 ml), place it in a planetary ball mill, and after ball milling for 72 hours, put the mixture into a drying oven and keep it at 70°C for 24 hours. Then put it into a box furnace for sintering, increase the temperature to 1400°C at 3°C / min and keep it for 5 hours. Take out the sample, repeat the above steps again, and finally sieve the powder with a stainless steel sieve (200 mesh) to obtain polycrystalline powder.
[0050] (2) Weigh 10 g of the polycrystalline powder obtained in step (1) and put it into a mold with a diameter of 25 mm. Use a hydraulic press to press the powder into a round blank with a diameter of 40 mm and a thickness of 3 mm after isostatic pressing at 12 MPa for 3 min. Then, vacuum seal the blank. Finally, cold isostatic press the packaged blank at 200 MPa for 3 min to complete the blank plasticization. The final blank diameter is 23.61 mm.
[0051] (3) The plasticized green blank was placed in a muffle furnace and heated to 600°C at 3°C / min and kept at this temperature for 5 h. The green blank and zirconium oxide powder were then placed in a tungsten crucible in the order of zirconium oxide powder (150 g), green blank, and zirconium oxide powder (150 g). -5 MPa), the temperature was raised at 3°C / min, and the temperature was kept at 1800-1850°C for 10 hours. After sintering, the sample was placed in a box furnace for annealing, the temperature was raised to 1250°C at 2°C / min, and the temperature was kept constant for 10 hours to eliminate internal defects, and finally the temperature was slowly lowered to room temperature, and the sample was taken out to complete the ceramic preparation.
[0052] (4) The ceramic sample is placed in a double-sided polishing machine for double-sided polishing. After polishing, the ceramic sample has a diameter of 20 mm and a thickness of 2.5 mm.
[0053] Example 5
[0054] This embodiment provides a method for preparing a pyrochlore-type Tb2Zr2O7 transparent ceramic material, and the specific steps are as follows:
[0055] (1) Preparation of Tb2Zr2O7 powder, the specific steps are as follows: according to the stoichiometric ratio, high-purity ZrO2 (Aladdin, purity 99.99%) and Tb4O7 (Changting Jinlong Rare Earth, purity 99.99%) are accurately weighed in a glove box, these raw materials (30 g) are placed in a zirconia ball mill, and zirconia balls (a total of 810 g) are added, wherein the ratio of large balls (diameter 10 mm), medium balls (diameter 8 mm), and small balls (diameter 3 mm) is 2:5:3, and the ball-to-material mass ratio is 27:1 , add dispersant polyethylene glycol (PEG400, dosage: 3 ml) and solvent anhydrous ethanol (C2H6O, dosage: 120 ml), place it in a planetary ball mill, and after ball milling for 72 hours, put the mixture into a drying oven and keep it at 70°C for 24 hours. Then put it into a box furnace for sintering, increase the temperature to 1400°C at 3°C / min and keep it for 5 hours. Take out the sample, repeat the above steps again, and finally sieve the powder with a stainless steel sieve (200 mesh) to obtain polycrystalline powder.
[0056] (2) Weigh 15 g of the polycrystalline powder obtained in step (1) and load it into a mold with a diameter of 40 mm. Use a hydraulic press to press the powder into a round blank with a diameter of 40 mm and a thickness of 5 mm after isostatic pressing at 12 MPa for 3 min. Then, vacuum seal the blank. Finally, cold isostatic press the packaged blank at 200 MPa for 3 min to complete the blank plasticization. The final blank diameter is 36 mm.
[0057] (3) The plasticized green blank was placed in a muffle furnace and heated to 600°C at 3°C / min and kept at this temperature for 5 h. The green blank and zirconium oxide powder were then placed in a tungsten crucible in the order of zirconium oxide powder (150 g), green blank, and zirconium oxide powder (150 g). -5 MPa), the temperature was raised at 3°C / min, and the temperature was kept at 1800-1850°C for 10h. After sintering, the sample was placed in a box furnace and annealed with flowing N2, and the temperature was raised to 1250°C at 2°C / min and kept at this temperature for 10h to eliminate internal defects. Finally, the temperature was slowly lowered to room temperature, and the sample was taken out to complete the ceramic preparation.
[0058] (4) The ceramic sample is placed in a double-sided polishing machine for double-sided polishing. After polishing, the ceramic sample has a diameter of 20 mm and a thickness of 2.5 mm.
[0059] The pyrochlore type A 2-x B x Zr2O7 transparent ceramic material has Figure 2 The X-ray powder diffraction pattern is shown.
[0060] The transmittance of the green stone transparent ceramic material is 65% to 76% @ 1550nm.
[0061] The pyrochlore type A 2-x B x Zr2O7 transparent ceramic material has Figure 3 The transmittance spectrum is shown.
[0062] The size of the pyrochlore type transparent ceramic material is 20 mm to 30 mm.
[0063] The pyrochlore type A 2-x B x Zr2O7 transparent ceramic material has Figure 4 Actual picture shown.
[0064] The pyrochlore type A provided by the present invention 2-x B x Zr2O7 transparent ceramic material has high raw material utilization rate and high optical transmittance, and can be doped with a variety of rare earths to form pyrochlore A 2-x B x Zr2O7 transparent ceramic materials are modified to meet different application requirements.
[0065] The pyrochlore type A provided by the present invention 2-x B x The invention relates to a method for preparing Zr2O7 ceramic material. The method prepares powder by a solid phase method, and then prepares transparent ceramic material by sintering in a vacuum tungsten wire furnace. In particular, in the raw material preparation process, a secondary ball milling process is adopted to obtain powder with a more uniform particle size, and then vacuum sintering is performed to prepare a transparent ceramic material with high transmittance. The method has the advantages of being simple and efficient, having a high raw material utilization rate, and being suitable for large-scale industrial production.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A pyrochlore type A 2-x B x Zr2O7 transparent ceramic material, characterized by: A and B are independently selected from at least one of the trivalent elements Gd, Eu, Al, and Tb. The transparent ceramics prepared using Gd, Eu, and Al have X-ray detection capabilities, and the transparent ceramics prepared using Tb have magneto-optical properties.
2. A pyrochlore type A according to claim 1 2-x B x Zr2O7 transparent ceramic material, characterized by: According to actual needs, transparent ceramic materials for different applications can be prepared by doping with different rare earth ions.
3. A pyrochlore type A according to claim 1 2-x B x Zr2O7 transparent ceramic material, characterized by: 0≤x≤2。 4. A pyrochlore type A according to claim 1 2-x B x Zr2O7 transparent ceramic material, characterized by: The crystal structure is cubic.
5. A pyrochlore type A as claimed in any one of claims 1 to 4 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by: The method comprises two process steps: preparing powder by solid phase method and preparing transparent ceramic material by vacuum sintering.
6. The pyrochlore type A according to claim 5 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by: The specific method for preparing the powder is as follows: The required raw materials were weighed according to the stoichiometric ratio, loaded into a ball mill, and zirconium oxide balls, anhydrous ethanol and polyethylene glycol were added. After ball milling for a certain period of time, the mixture was placed in an oven, and then the dried powder was sieved. The obtained powder was then sintered in a box furnace, and the temperature was increased to 1200-1500°C at 2-3°C / min and kept for 5-8h. The above operation was repeated again to obtain A 2-x B x Zr2O7 polycrystalline powder; the polycrystalline powder is pressed into a round blank with a diameter of 10 to 60 mm and a thickness of 3 to 10 mm by a hydraulic press, and then the blank is vacuum packaged, and finally the packaged blank is cold isostatically pressed at 200 to 250 MPa for 2 to 3 minutes to complete the blank plasticity.
7. The pyrochlore type A according to claim 6 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by: A2O3, B2O3 rare earth oxides and ZrO2 are weighed according to the stoichiometric ratio and loaded into the zirconium oxide spherical ink tank.
8. A pyrochlore type A according to claim 6 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by: The diameter of the large zirconia ball is 10-12 mm, the diameter of the medium ball is 6-8 mm, and the diameter of the small ball is 2-5 mm. The mass ratio of the large, medium and small balls is 1-2:5-6:2-3, and the ratio of the total mass of the zirconia ball to the mass of the raw materials is 25-28:
1.
9. A pyrochlore type A according to claim 6 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by: The plasticized green embryo is heated to 600-900°C at 2-3°C / min and kept at a constant temperature for 5-6 hours. The zirconia powder and green embryo samples are placed in a tungsten crucible and sintered in a vacuum tungsten wire furnace. The temperature is increased at 2-3°C / min and kept at a temperature range of 1800-1850°C for 10-50 hours. After sintering, it is placed in a box furnace for annealing, heated to 1200-1450°C at 2-3°C / min, kept at a constant temperature for 10-30 hours, and finally slowly cooled to room temperature.
10. A pyrochlore type A according to claim 5 2-x B x The method for preparing Zr2O7 transparent ceramic material is characterized by: The contents of anhydrous ethanol and polyethylene glycol are determined according to the volume of the ball ink tank.